Catalyst for selective catalytic reduction of NOx
A catalyst with a specific substrate and coating composition effectively addresses the challenge of high NOx conversion and reduced N2O formation, meeting stringent emission standards by enhancing both conversion efficiency and thermal stability.
Patent Information
- Application Number
- CN202380038024.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-22
- Filing Date
- 2023-04-21
- Publication Date
- 2024-12-17
AI Technical Summary
Existing technologies have not adequately addressed the challenges of existing technologies have not adequately addressed the need for a catalyst that achieves high NOx conversion while minimizing the formation of nitrous oxide (N2O) emissions and reducing the formation of nitrous oxide (N2O) emissions, particularly under stringent regulatory standards like Euro 7.
A catalyst comprising a substrate with a coating of zeolitic material, copper, and a non-zeolitic oxidic material containing iron and aluminum, with specific ratios and compositions, is developed to enhance NOx conversion and reduce N2O formation across a wide temperature range, featuring improved thermal stability.
The catalyst achieves high NOx conversion rates and significantly reduces N2O emissions, demonstrating improved performance and stability compared to prior art catalysts.
Smart Images

Figure HDA0005114685700000011 
Figure HDA0005114685700000021 
Figure HDA0005114685700000031
Abstract
Description
[0001] The present invention relates to a catalyst for selective catalytic reduction of NOx, a method for preparing a catalyst for selective catalytic reduction of NOx, a catalyst obtained by the method and uses of the catalyst of the present invention.
[0002] Copper-based selective catalytic reduction catalysts (SCR) and selective catalytic reduction catalysts (SCRoF) on filters are known in the art and provide good NOx conversion. In this regard, US 9 242 238 B2 discloses a mixed catalyst comprising 8-ring small-pore molecular sieves promoted by copper and 8-ring small-pore molecular sieves promoted by iron. In addition, US9 352 307 B2 discloses a SCR catalyst comprising a mixture of Cu-CHA and Fe-MFI for improving NOx conversion, and US 9 999 877 B2 discloses a mixed zeolite catalyst Cu-CHA / Fe-BEA for treating NOx in a gas stream.
[0003] However, in view of increasingly stringent regulations, in particular those towards Euro 7, a good NOx conversion is not enough and limiting N2O emissions is also becoming very important, so there is a need to provide a new catalyst for the selective catalytic reduction of NOx which exhibits a high NOx conversion and reduces the formation of nitrous oxide (N2O).
[0004] Therefore, an object of the present invention is to provide a novel catalyst for the selective catalytic reduction of NOx, which shows a high NOx conversion rate and reduces the formation of nitrous oxide (N2O). Surprisingly, it has been found that the catalyst of the present invention allows to show a high NOx conversion rate and reduce N2O in a wide temperature range. In addition, compared with the prior art, the catalyst has an improved thermal stability.
[0005] Therefore, the present invention relates to a catalyst for selective catalytic reduction of NOx, the catalyst comprising
[0006] a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough;
[0007] A coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25% by weight of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3.
[0008] Pages Public Figure: AB W、ACO、AEI、AEL、AEN、AET、AFG、AFI、A FN、AFO、AFR、AFS、AFT、AFV、AFX、AFY、AHT、ANA、APC、APD、AST、ASV、ATN、ATO ATS、ATT、ATV、AVL、AWO、AWW、BCT、BEA、BEC、BIK、BOF、BOG、BOZ、BPH、BRE、 BSV、CAN、CAS、CDO、CFI、CGF、CGS、CHA、-CHI、-CLO、CON、CSV、CZP、DAC、DDR、 DFO、DFT、DOH、DON、EAB、EDI、EEI、EMT、EON、EPI、ERI、ESV、ETR、EUO、*-EWT 、EZT、FAR、FAU、FER、FRA、GIS、GIU、GME、GON、GOO、HEU、IFO、IFR、-IFU、IFW、 IFY、IHW、IMF、IRN、IRR、-IRY、ISV、ITE、ITG、ITH、*-ITN、ITR、ITT、-ITV、IT W, IWR, IWS, IWV, IWW, JBW, JNT, JOZ, JRY, JSN, JSR, JST, JSW, KFI, LAU, LEV. LIO、-LIT、LOS、LOV、LTA、LTF、LTJ、LTL、LTN、MAR、MAZ、MEI、MEL、MEP、MER、 MFI、MFS、MON、MOR、MOZ、*MRE、MSE、MSO、MTF、MTN、MTT、MTW、MVY、MWF、MWW、N AB、NAT、NES、NON、NPO、NPT、NSI、OBW、OFF、OKO、OSI、OSO、OWE、-PAR、PAU、P CR、PHI、PON、POS、PSI、PUN、RHO、-RON、RRO、RSN、RTE、RTH、RUT、RWR、RWY、SA F, SAO, SAS, SAT, SAV, SBE, SBN, SBS, SBT, SEW, SFE, SFF, SFG, SFH, SFN, SFO 、SFS、*SFV、SFW、SGT、SIV、SOD、SOF、SOS、SSF、*-SSO、SSY、STF、STI、*STO、S TT、STW、-SVR、SVV、SZR、TER、THO、TOL、TON、TSC、TUN、UEI、UFI、UOS、UOV、UO Z, USI, UTL, UWY, VET, VFI, VNI, VSV, WEI, -WEN, YUG, ZONand a mixed type of two or more thereof; more preferably selected from CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, a mixture of two or more thereof, and a mixed type of two or more thereof; more preferably selected from CHA, AEI, RTH, AFX, a mixture of two or more thereof, and a mixed type of two or more thereof; more preferably selected from CHA and AEI. More preferably, the zeolite material contained in the coating has a framework type CHA. ,
[0009] Preferably 95 to 100 wt %, more preferably 98 to 100 wt %, more preferably 99 to 100 wt % of the framework structure of the zeolitic material consists of Si, Al and O.
[0010] Preferably, in the framework structure of the zeolite material contained in the coating, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 2:1 to 30:1, more preferably in the range of 5:1 to 28:1, more preferably in the range of 8:1 to 26:1. More preferably, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 10:1 to 19:1, more preferably in the range of 12:1 to 18:1. Alternatively, more preferably, the molar ratio of Si to Al calculated as molar SiO2:Al2O3 is in the range of 20:1 to 25:1.
[0011] Preferably, the zeolitic material, more preferably a zeolitic material having the framework type CHA, comprised in the coating has an average crystallite size of at least 0.1 micrometer, more preferably in the range of 0.1 micrometer to 3.0 micrometers, more preferably in the range of 0.3 micrometer to 1.5 micrometers, more preferably in the range of 0.4 micrometer to 1.0 micrometer, as determined via scanning electron microscopy.
[0012] Preferably, the amount of copper contained in the coating is in the range of 2 wt.-% to 10 wt.-%, preferably in the range of 2.5 wt.-% to 8 wt.-%, more preferably in the range of 3 wt.-% to 7 wt.-%, more preferably in the range of 3.5 wt.-% to 6 wt.-%, calculated as CuO, based on the weight of the zeolite material.
[0013] Preferably, the zeolite material contained in the coating contains copper.
[0014] Preferably, the zeolitic material comprises iron, wherein the amount of iron contained in the zeolitic material, calculated as Fe2O3, based on the weight of the zeolitic material, is more preferably in the range of 0.1 wt.% to 1.5 wt.%, more preferably in the range of 0.15 wt.% to 1.25 wt.%, more preferably in the range of 0.25 wt.% to 1 wt.%, more preferably in the range of 0.3 wt.% to 0.8 wt.%.
[0015] Preferably, the zeolite material comprises copper and iron. Preferably, the present invention relates to a catalyst for selective catalytic reduction of NOx, the catalyst comprising
[0016] a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough;
[0017] a coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25% by weight of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3;
[0018] Wherein the copper is contained in a zeolite material and the zeolite material contains iron.
[0019] Alternatively, the zeolitic material is preferably substantially free of iron, more preferably free of iron. In other words, preferably 0 wt% to 0.001 wt%, more preferably 0 wt% to 0.0001 wt% of the zeolitic material consists of iron calculated as Fe2O3.
[0020] Preferably, the coating comprises a loading of 0.25 g / in 3 Up to 5g / in 3 In the range of 0.75 g / in 3 Up to 3g / in 3 In the range of 1 g / in 3 Up to 2.5g / in 3 In the range of 1.25 g / in 3 Up to 2.2g / in 3 range of zeolite materials.
[0021] Preferably, the zeolitic material contained in the coating, more preferably of framework type CHA, has a relative humidity at 50 m / s determined as described in reference example 1. 2 / g to 900m 2 / g, more preferably 150 m 2 / g to 700m 2 / g, more preferably within 250 m 2 / g to 650m 2 / g in the range of BET specific surface area.
[0022] Preferably 50 to 92 wt. %, more preferably 65 to 90 wt. %, more preferably 70 to 85 wt. % of the coating consists of zeolitic material.
[0023] More preferably, when the substrate of the catalyst of the present invention is a flow-through substrate, 80 wt % to 85 wt % of the coating consists of zeolite material. Alternatively, when the substrate of the catalyst of the present invention is a wall-flow filter substrate, more preferably 72 wt % to 78 wt % of the coating consists of zeolite material.
[0024] Preferably, 25 to 65 wt.-%, more preferably 30 to 60 wt.-%, more preferably 40 to 55 wt.-%, more preferably 45 to 55 wt.-% of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3.
[0025] Preferably, 35 to 75 wt.-%, more preferably 40 to 70 wt.-%, more preferably 45 to 60 wt.-%, more preferably 45 to 55 wt.-% of the first non-zeolitic oxidic material consists of aluminium calculated as Al2O3.
[0026] Preferably, in the first non-zeolitic oxide material, the weight ratio of aluminium to iron, calculated as the weight Al2O3:Fe2O3 ratio, is in the range of 0.5:1 to 3:1, preferably in the range of 2.33:1 to 1.5:1, more preferably in the range of 0.8:1 to 1.2:1, more preferably in the range of 0.9:1 to 1.1:1.
[0027] Preferably, the first non-zeolitic oxide material is one or more of an oxide mixture comprising Al and Fe, a mixed oxide comprising Al and Fe, and Al oxide impregnated with Fe, more preferably one or more of a mixed oxide comprising Al and Fe, and Al oxide impregnated with Fe.
[0028] Preferably, the first non-zeolitic oxidic material has a 2 / g to 300m 2 / g, more preferably in the range of 80m 2 / g to 160m 2 / g in the range of BET specific surface area.
[0029] Preferably, the coating comprises the first non-zeolitic oxidic material in an amount in the range of 5 to 20 wt%, more preferably in the range of 7 to 15 wt%, more preferably in the range of 8 to 12 wt%, based on the weight of the zeolitic material.
[0030] Preferably, the present invention relates to a catalyst for selective catalytic reduction of NOx, the catalyst comprising
[0031] a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough;
[0032] a coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25% by weight of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3;
[0033] Wherein the coating comprises the first non-zeolitic oxide material in an amount ranging from 5 wt % to 20 wt %, more preferably ranging from 7 wt % to 15 wt %, more preferably ranging from 8 wt % to 12 wt %, based on the weight of the zeolitic material.
[0034] Preferably, the present invention relates to a catalyst for selective catalytic reduction of NOx, the catalyst comprising
[0035] a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough;
[0036] a coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25% by weight of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3;
[0037] wherein the coating comprises the first non-zeolitic oxidic material in an amount ranging from 5 wt % to 20 wt %, more preferably ranging from 7 wt % to 15 wt %, more preferably ranging from 8 wt % to 12 wt %, based on the weight of the zeolitic material;
[0038] The zeolite material has a framework type selected from CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from CHA, AEI, RTH, AFX, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from CHA and AEI, and the zeolite material contained in the coating has a framework type CHA.
[0039] In the context of the present invention, preferably, in the catalyst, the weight ratio of the zeolitic material relative to the first non-zeolitic oxidic material is in the range of 5:1 to 20:1, more preferably in the range of 6.7:1 to 14.3:1, more preferably in the range of 8.3:1 to 12.5:1.
[0040] Preferably, the present invention relates to a catalyst for selective catalytic reduction of NOx, the catalyst comprising
[0041] a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough;
[0042] a coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25% by weight of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3;
[0043] Wherein in the catalyst, the weight ratio of the zeolite material to the first non-zeolite oxide material is in the range of 5:1 to 20:1, more preferably in the range of 6.7:1 to 14.3:1, and more preferably in the range of 8.3:1 to 12.5:1.
[0044] Preferably, the present invention relates to a catalyst for selective catalytic reduction of NOx, the catalyst comprising
[0045] a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough;
[0046] a coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25% by weight of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3;
[0047] wherein in the catalyst, the weight ratio of the zeolitic material to the first non-zeolitic oxidic material is in the range of 5:1 to 20:1, more preferably in the range of 6.7:1 to 14.3:1, more preferably in the range of 8.3:1 to 12.5:1;
[0048] The zeolite material has a framework type selected from CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from CHA, AEI, RTH, AFX, a mixture of two or more thereof and a mixed type of two or more thereof, more preferably selected from CHA and AEI, and the zeolite material contained in the coating has a framework type CHA.
[0049] In the context of the present invention, preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-%, more preferably 99.9 to 100 wt.-% of the first non-zeolitic oxidic material consists of Al, Fe and O. In other words, the first non-zeolitic oxidic material preferably consists essentially of Al, Fe and O, more preferably consists of Al, Fe and O.
[0050] Preferably, 0 to 0.01 wt. %, more preferably 0 to 0.001 wt. %, more preferably 0 to 0.0001 wt. % of the first non-zeolitic oxidic material consists of cerium calculated as CeO2. In other words, the non-zeolitic oxidic material is preferably substantially free of cerium, more preferably free of cerium.
[0051] Preferably, the coating further comprises a second non-zeolitic oxide material, which more preferably comprises one or more of zirconia, alumina, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ti and Si, more preferably comprises one or more of silica, alumina and zirconia, more preferably comprises one or more of alumina and zirconia, more preferably zirconia.
[0052] Preferably, 95 to 100 wt.-%, more preferably 98 to 100 wt.-%, more preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-% of the second non-zeolitic oxidic material is contained in the coating consisting of zirconium calculated as ZrO. In other words, the second non-zeolitic oxidic material contained in the coating preferably consists essentially of zirconium oxide, more preferably consists of zirconium oxide.
[0053] Preferably, the coating comprises the second non-zeolitic oxidic material in an amount ranging from 2 wt% to 40 wt%, more preferably ranging from 2.5 wt% to 30 wt%, more preferably ranging from 3 wt% to 25 wt%, based on the weight of the zeolitic material. More preferably, the coating comprises the second non-zeolitic oxidic material in an amount ranging from 3 wt% to 10 wt%, more preferably ranging from 3.5 wt% to 7 wt%, based on the weight of the zeolitic material; or the coating more preferably comprises the second non-zeolitic oxidic material in an amount ranging from 15 wt% to 25 wt%, more preferably ranging from 17 wt% to 22 wt%, based on the weight of the zeolitic material.
[0054] More preferably, when the substrate of the catalyst of the present invention is a flow-through substrate, the coating comprises the second non-zeolitic oxidic material in an amount ranging from 3 wt% to 10 wt%, more preferably ranging from 3.5 wt% to 7 wt%, based on the weight of the zeolitic material. Alternatively, when the substrate of the catalyst of the present invention is a wall-flow filter substrate, the coating comprises the second non-zeolitic oxidic material in an amount ranging from 15 wt% to 25 wt%, more preferably ranging from 17 wt% to 22 wt%, based on the weight of the zeolitic material.
[0055] Preferably, 98 to 100 wt. %, more preferably 99 to 100 wt. %, more preferably 99.5 to 100 wt. %, more preferably 99.9 to 100 wt. % of the coating consists of copper, the zeolitic material optionally comprising iron, the first non-zeolitic oxidic material comprising Fe and Al, and more preferably the second non-zeolitic oxidic material as defined above. In other words, it is preferred that the coating consists essentially of copper, more preferably consists of copper, the zeolitic material optionally comprising iron, the first non-zeolitic oxidic material comprising Fe and Al, and more preferably the second non-zeolitic oxidic material as defined above.
[0056] Preferably, the substrate is made of one or more of cordierite, silicon carbide, and aluminum titanate, more preferably one or more of cordierite and silicon carbide, and more preferably cordierite or silicon carbide.
[0057] Preferably, according to the first aspect of the invention, the substrate is a wall flow filter substrate, wherein the plurality of channels comprises inlet channels having an open inlet end and a closed outlet end, and outlet channels having a closed inlet end and an open outlet end.
[0058] Preferably, the wall flow filter substrate is made of one or more of silicon carbide and aluminum titanate, more preferably made of silicon carbide.
[0059] Preferably, the coating is located within the porous walls of the wall flow filter substrate.
[0060] Preferably, according to the first aspect of the invention, the coating is uniformly disposed along the substrate axial length. Alternatively, preferably, the amount of coating in the middle region of the substrate axial length is higher than the amount present at each of the inlet end of the substrate and the outlet end of the substrate. More preferably, according to the first aspect of the invention, the amount of coating in the middle region of the substrate axial length is higher than the amount present at each of the inlet end of the substrate and the outlet end of the substrate. The following examples illustrate this point.
[0061] Preferably, according to the first aspect, the substrate comprises a coating having a loading of 0.5 g / in 3 Up to 3g / in 3 In the range of 0.75 g / in 3 Up to 2.5g / in 3 In the range of 1g / in 3 Up to 2g / in 3 within the range.
[0062] Preferably, according to the second aspect of the present invention, the substrate is a flow-through substrate. More preferably, the flow-through substrate is made of cordierite.
[0063] Preferably, according to the second aspect, the coating is located on the surface of the inner wall of the substrate.
[0064] Preferably, according to said second aspect, the coating is uniformly disposed along the axial length of the substrate.
[0065] Preferably, according to the second aspect, the substrate comprises a coating having a loading of 0.75 g / in 3 Up to 5.5g / in 3 In the range of 1.25 g / in 3 Up to 4.5g / in 3 In the range of 2 g / in 3 Up to 4g / in 3 within the range.
[0066] In the context of the present invention, the coating is preferably provided over more than 98% to 100%, more preferably more than 99% to 100%, of the axial length of the substrate.
[0067] Preferably, the catalyst of the present invention consists of a substrate and a coating.
[0068] Furthermore, the present invention relates to a method for preparing a catalyst for the selective catalytic reduction of NOx, more preferably a catalyst according to the present invention, the method comprising
[0069] (i) preparing a first aqueous mixture comprising water, a copper source and, optionally, a precursor of a second non-zeolitic oxidizing component;
[0070] (ii) mixing the first aqueous mixture obtained according to (i) with water and a zeolite material to obtain a second aqueous mixture, wherein the zeolite material does not contain copper, and wherein the zeolite material optionally comprises iron;
[0071] (iii) mixing a first non-zeolitic oxidic material comprising Al and Fe, wherein at least 25 wt. % of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3, with the second aqueous mixture prepared according to (ii), preferably adding water, to obtain a third aqueous mixture;
[0072] (iv) disposing the third aqueous mixture obtained according to (iii) on a substrate comprising an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels extending therethrough defined by an inner wall of the substrate; and optionally drying the substrate comprising the mixture;
[0073] (v) calcining the substrate obtained in (iv).
[0074] Preferably, the copper source contained in the first aqueous mixture prepared in (i) is selected from copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide and a mixture of two or more thereof, more preferably selected from copper acetate, copper oxide and a mixture thereof, more preferably copper oxide, more preferably CuO.
[0075] Preferably, the precursor of the second non-zeolitic oxidic component comprised in the first aqueous mixture prepared in (i) is a zirconium salt or zirconium oxide, more preferably a zirconium salt, more preferably zirconium acetate.
[0076] Preferably, the first aqueous mixture prepared in (i) comprises copper, calculated as CuO, in an amount in the range of 2 to 10 wt.-%, more preferably in the range of 2.5 to 8 wt.-%, more preferably in the range of 3 to 7 wt.-%, more preferably in the range of 3.5 to 6 wt.-%, based on the weight of the zeolitic material contained in the second aqueous mixture prepared in (ii).
[0077] Preferably, (i) comprises
[0078] (i.1) preparing a mixture comprising water and the copper source, the mixture more preferably further comprising an acid, more preferably an organic acid, more preferably acetic acid; wherein the mixture optionally and more preferably further comprises sucrose; (i.2) adding the precursor of the second non-zeolitic oxidation component to the mixture obtained according to (i.1) to obtain the first aqueous mixture.
[0079] With regard to (i.1), when the substrate used in (iv) is a wall flow filter substrate, the mixture prepared according to (i.1) preferably comprises sucrose.
[0080] More preferably, the amount of sucrose present in the mixture prepared in (i.1) is in the range of 2 wt.% to 10 wt.%, more preferably in the range of 2.5 wt.% to 8 wt.%, more preferably in the range of 3 wt.% to 7 wt.%, more preferably in the range of 3.5 wt.% to 6 wt.%, based on the weight of the zeolitic material contained in the second aqueous mixture prepared in (ii).
[0081] More preferably, the weight ratio of copper calculated as CuO to sucrose is in the range of 2:1 to 1:2, more preferably in the range of 1.5:1 to 1:1.5, more preferably in the range of 1.2:1 to 1:1.2.
[0082] Preferably 90 to 100% by weight, more preferably 93 to 99% by weight, more preferably 96 to 99% by weight, of the copper source is present in an undissolved state in the mixture prepared in (i.1).
[0083] Preferably, the copper particles in the mixture according to (i.1) have a Dv90 in the range of 0.1 μm to 15 μm, more preferably in the range of 0.5 μm to 10 μm, more preferably in the range of 1 μm to 8 μm, more preferably in the range of 3 μm to 7 μm, the Dv90 being preferably determined as described in Reference Example 3.
[0084] Preferably, the second mixture obtained in (ii) has a solid content in the range of 15 wt % to 50 wt %, more preferably in the range of 20 wt % to 45 wt %, more preferably in the range of 30 wt % to 40 wt %, based on the weight of the second mixture.
[0085] Preferably, the zeolitic material particles in the second mixture have a Dv50 in the range of 0.5 microns to 5 microns, preferably in the range of 0.75 microns to 3 microns, the Dv90 is preferably determined as described in Reference Example 3.
[0086] Preferably, (ii) comprises
[0087] (ii.1) mixing the first aqueous mixture obtained according to (i) with water and a zeolite material, wherein
[0088] The zeolite material is free of copper, and wherein the zeolite material optionally comprises iron;
[0089] (ii.2) grinding the obtained mixture (ii.1), more preferably until the mixture particles have a Dv90 in the range of 0.5 μm to 8 μm, more preferably in the range of 1 μm to 5 μm, more preferably in the range of 1.5 μm to 4 μm, the Dv90 preferably being determined as described in Reference Example 3, to obtain the third aqueous mixture;
[0090] Wherein more preferably the particles of the mixture have a Dv99 in the range of 1.5 microns to 12 microns, more preferably in the range of 2 microns to 10 microns, more preferably in the range of 3 microns to 7 microns, and the Dv99 is preferably measured as described in Reference Example 3 to obtain the second aqueous mixture.
[0091] Preferably, the particles of the first non-zeolitic oxidic material mixed with the second aqueous mixture according to (ii) have a Dv50 in the range of 3 to 15 microns, more preferably in the range of 6 to 12 microns, the Dv50 preferably being determined as described in Reference Example 3.
[0092] Preferably, the particles of the first non-zeolitic oxidic material mixed with the second aqueous mixture according to (ii) have a Dv90 in the range of 8 to 40 microns, more preferably in the range of 15 to 25 microns, the Dv90 being preferably determined as described in Reference Example 3.
[0093] Preferably, the particles of the first non-zeolitic oxidic material mixed with the second aqueous mixture according to (ii) have a Dv99 in the range of 10 microns to 50 microns, more preferably in the range of 20 microns to 30 microns, the Dv99 being preferably determined as described in Reference Example 3.
[0094] Preferably, the mixture prepared in (iii) comprises the first non-zeolitic oxidic material in an amount in the range of 5 wt.-% to 20 wt.-%, more preferably in the range of 7 wt.-% to 15 wt.-%, more preferably in the range of 8 wt.-% to 12 wt.-%, based on the weight of the zeolitic material.
[0095] Preferably, the third aqueous mixture obtained in (iii) has a solid content in the range of 15 wt % to 50 wt %, more preferably in the range of 25 wt % to 48 wt %, more preferably in the range of 28 wt % to 40 wt %, based on the weight of the third aqueous mixture.
[0096] Preferably, 98 to 100 wt.-%, more preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-%, more preferably 99.9 to 100 wt.-% of the third aqueous mixture obtained according to (iii) consists of water, the zeolitic material optionally comprising iron, the copper source, the first non-zeolitic oxidic material comprising Al and Fe, and more preferably the precursor of the second non-zeolitic oxidic material. In other words, the third aqueous mixture obtained according to (iii) preferably consists essentially of water, the zeolitic material optionally comprising iron, the copper source, the first non-zeolitic oxidic material comprising Al and Fe, and more preferably the precursor of the second non-zeolitic oxidic material, and more preferably consists of water.
[0097] Preferably, the providing of the mixture according to (iv) is performed by spraying the third mixture onto the substrate or by dipping the substrate into the mixture, more preferably by dipping the substrate into the mixture.
[0098] Preferably, the third aqueous mixture obtained according to (iii) is arranged according to (iv) within the range of x% of the axial length of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, wherein x is in the range of 95 to 100, more preferably in the range of 98 to 100, and more preferably in the range of 99 to 100.
[0099] Preferably, the substrate in step (iv) is a flow-through substrate, which is more preferably made of one or more of cordierite, silicon carbide and aluminum titanate, more preferably made of one or more of cordierite and silicon carbide, and more preferably made of cordierite.
[0100] Preferably, (iv) comprises
[0101] disposing the third aqueous mixture obtained according to (iii) on a flow-through substrate over 95% to 100%, more preferably 98% to 100%, more preferably 99% to 100% of the axial length of the substrate from the inlet end towards the outlet end of the substrate or from the outlet end towards the inlet end, more preferably from the inlet end towards the outlet end; and drying the substrate comprising said mixture;
[0102] Preferably, the substrate in (iv) is a wall flow filter substrate, wherein the multiple channels include an inlet channel having an open inlet end and a closed outlet end, and an outlet channel having a closed inlet end and an open outlet end, and the substrate is more preferably made of one or more of cordierite, silicon carbide and aluminum titanate, and more preferably made of one or more of silicon carbide and aluminum titanate.
[0103] Preferably, the arrangement according to (iv) comprises
[0104] (iv.1) placing the first portion of the third aqueous mixture obtained in (iii) on a wall flow filter substrate, with the substrate axially extending from the outlet end of the substrate toward the inlet end.
[0105] The length is 40% to 85%, more preferably 55% to 80%, more preferably 65% to 75%;
[0106] and drying said substrate comprising said first portion of said third aqueous mixture;
[0107] (iv.2) placing the second part of the third aqueous mixture obtained in (iii) in a
[0108] (iv.1) on the substrate of the first part of the third aqueous mixture obtained, the axial length of the substrate from the inlet end of the substrate toward the outlet end is 40 to 85%, more preferably 55 to 80%, more preferably 65 to 75%, and the substrate comprising the first part and the second part of the third aqueous mixture is optionally dried.
[0109] As an alternative, it is conceivable that the first part is applied over 100% of the axial length of the substrate starting from the inlet end or the outlet end of the substrate, and the second part is applied over 100% of the axial length of the substrate starting from the other end of the inlet end or the outlet end of the substrate. It is also conceivable that in (iv.1), the arrangement is made from the inlet end toward the outlet end, and in (iv.2), the arrangement is made from the outlet end toward the inlet end.
[0110] In the context of the present invention, drying according to (iv) is preferably carried out in a gas atmosphere having a temperature in the range of 60 to 300°C, more preferably in the range of 90 to 150°C, the gas atmosphere more preferably comprising oxygen.
[0111] When (iv) includes (iv.1) and (iv.2), it is preferred that the drying according to (iv.1) and / or (iv.2), more preferably according to (iv.1) and (iv.2), is carried out in a gas atmosphere having a temperature in the range of 60° C. to 300° C., more preferably in the range of 90° C. to 150° C. Preferably, the drying according to (iv) is carried out in a gas atmosphere for a duration in the range of 10 minutes to 4 hours, more preferably in the range of 20 minutes to 2 hours.
[0112] When (iv) includes (iv.1) and (iv.2), it is preferred that the drying according to (iv.1) and / or (iv.2), more preferably according to (iv.1) and (iv.2), is carried out in a gas atmosphere for a duration in the range of 10 minutes to 4 hours, more preferably in the range of 20 minutes to 2 hours.
[0113] Preferably, the calcination according to (v) is carried out in a gas atmosphere having a temperature in the range of 300 to 900°C, more preferably in the range of 400 to 650°C, more preferably in the range of 400 to 500°C, the gas atmosphere more preferably comprising oxygen.
[0114] Preferably, the calcination according to (v) is carried out in a gas atmosphere for a duration ranging from 0.1 hours to 4 hours, more preferably ranging from 0.5 hours to 2.5 hours.
[0115] Preferably, the method of the present invention consists of (i), (ii), (iii), (iv) and (v).
[0116] The present invention also relates to a catalyst for the selective catalytic reduction of NOx, which catalyst is obtainable or obtained by the method according to the present invention. The catalyst is preferably as defined above.
[0117] The invention also relates to an exhaust gas treatment system for treating exhaust gases leaving a compression ignition engine, more preferably a diesel engine, said exhaust gas treatment system having an upstream end for introducing said exhaust gas flow into said exhaust gas treatment system,
[0118] The exhaust gas treatment system comprises:
[0119] The catalyst according to the present invention and
[0120] One or more of a diesel oxidation catalyst, a selective catalytic reduction catalyst, an ammonia oxidation catalyst, a NOx trap and a particulate filter. Preferably, the system comprises a diesel oxidation catalyst, wherein the catalyst according to the present invention is located downstream of the diesel oxidation catalyst.
[0121] Preferably, the system comprises a diesel oxidation catalyst, a selective catalytic reduction catalyst on a filter and a catalyst according to the invention,
[0122] wherein the diesel oxidation catalyst is upstream of the selective catalytic reduction catalyst on the filter (SCRoF) and the catalyst according to the invention is downstream of the SCRoF catalyst;
[0123] The system may further comprise a selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the catalyst according to the invention.
[0124] Alternatively, preferably, the system comprises a diesel oxidation catalyst, a selective catalytic reduction catalyst and a catalyst according to the present invention, wherein the diesel oxidation catalyst is upstream of the selective catalytic reduction (SCR) catalyst and the catalyst according to the present invention is downstream of the SCR catalyst;
[0125] The system may further comprise a selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the catalyst according to the invention.
[0126] Alternatively, preferably, the system comprises a diesel oxidation catalyst, a selective catalytic reduction catalyst, a catalyst according to the present invention, wherein the diesel oxidation catalyst is upstream of the catalyst according to the present invention, and the selective catalytic reduction (SCR) catalyst is downstream of the catalyst according to the present invention;
[0127] The system further comprises an additional selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the SCR catalyst.
[0128] Alternatively, preferably, the system of the invention comprises a diesel oxidation catalyst, a selective catalytic reduction catalyst on a filter (SCRoF), a catalyst according to the invention, wherein the diesel oxidation catalyst is upstream of the catalyst according to the invention and the SCRoF catalyst is downstream of the catalyst according to the invention;
[0129] The system further comprises a selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the SCRoF catalyst.
[0130] The invention also relates to the use of the catalyst according to the invention for the selective catalytic reduction of NOx.
[0131] The present invention also relates to a method for selective catalytic reduction of NOx, the method comprising:
[0132] (1) providing an exhaust gas flow, preferably away from a diesel engine;
[0133] (2) The exhaust gas flow provided in (1) is brought into contact with the catalyst for selective catalytic reduction of NOx according to the present invention.
[0134] The invention is further illustrated by the following set of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where a range of embodiments is mentioned, for example in the context of a term such as "a catalyst according to any one of embodiments 1 to 4", each embodiment within the range is meant to be explicitly disclosed to the skilled person, i.e. the wording of the term should be understood by the skilled person as being synonymous with "a catalyst according to any one of embodiments 1, 2, 3 and 4". Furthermore, it should be explicitly pointed out that the following set of embodiments represents a properly structured part of a general description of preferred aspects of the invention and therefore properly supports but does not represent the claims of the invention.
[0135] 1. A catalyst for selective catalytic reduction of NOx, the catalyst comprising
[0136] a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough;
[0137] A coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25% by weight of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3.
[0138] 2. The catalyst according to embodiment 1, wherein the catalyst comprises the zeolite material in the coating having a skeleton type selected from the following: ABW, ACO, AEI, AEL, AEN, AET, AFG, AFI, AFN, AFO, AFR, AFS, AFT, AFV, AFX, AFY, AHT, ANA, APC , APD, AST, ASV, ATN, ATO, ATS, ATT, ATV, AVL, AWO, AWW, BCT, BEA, BEC, BIK, BOF, BOG, BOZ, BPH, BRE, BSV, CAN, CAS, CDO, CFI, CGF, CGS, CHA, -CHI, -CLO, C ON, CSV, CZP, DAC, DDR, DFO, DFT, DOH, DON, EAB, EDI, EEI, EMT, EON, EPI, ERI, ESV, ETR, EUO, *-EWT, EZT, FAR, FAU, FER, FRA, GIS, GIU, GME, GON, GOO, HEU , IFO, IFR, -IFU, IFW, IFY, IHW, IMF, IRN, IRR, -IRY, ISV, ITE, ITG, ITH, *-ITN, ITR, ITT, -ITV, ITW, IWR, IWS, IWV, IWW, JBW, JNT, JOZ, JRY, JSN, JSR, JS T、JSW、KFI、LAU、LEV、LIO、-LIT、LOS、LOV、LTA、LTF、LTJ、LTL、LTN、MAR、MAZ、MEI、MEL、MEP、MER、MFI、MFS、MON、MOR、MOZ、*MRE、MSE、MSO、MTF、MTN、MTT、 MTW, MVY, MWF, MWW, NAB, NAT, NES, NON, NPO, NPT, NSI, OBW, OFF, OKO, OSI, OSO, OWE, -PAR, PAU, PCR, PHI, PON, POS, PSI, PUN, RHO, -RON, RRO, RSN, RTE, RT H, RUT, RWR, RWY, SAF, SAO, SAS, SAT, SAV, SBE, SBN, SBS, SBT, SEW, SFE, SFF, SFG, SFH, SFN, SFO, SFS, *SFV, SFW, SGT, SIV, SOD, SOF, SOS, SSF, *-SSO, SSY , STF, STI, *STO, STT, STW, -SVR, SVV, SZR, TER, THO, TOL, TON, TSC, TUN, UEI, UFI, UOS, UOV, UOZ, USI, UTL, UWY, VET, VFI, VNI, VSV, WEI, -WEN, YUG, ZON,A mixture of two or more thereof, and a mixed type of two or more thereof; more preferably selected from CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, a mixture of two or more thereof, and a mixed type of two or more thereof; more preferably selected from CHA, AEI, RTH, AFX, a mixture of two or more thereof, and a mixed type of two or more thereof; more preferably selected from CHA and AEI. ,
[0139] 3. The catalyst according to embodiment 1 or 2, wherein 95 to 100 wt. %, preferably 98 to 100 wt. %, more preferably 99 to 100 wt. % of the framework structure of the zeolitic material consists of Si, Al and O, wherein the molar ratio of Si to Al in the framework structure, calculated as molar SiO2:Al2O3, is preferably in the range of 2:1 to 30:1, more preferably in the range of 5:1 to 28:1, more preferably in the range of 8:1 to 26:1,
[0140] More preferably in the range of 10:1 to 19:1, more preferably in the range of 12:1 to 18:1; or
[0141] More preferably, it is in the range of 20:1 to 25:1.
[0142] 4. The catalyst according to any one of embodiments 1 to 3, wherein the zeolite material contained in the coating, preferably the zeolite material having a framework type CHA, has an average crystallite size of at least 0.1 micrometer, preferably in the range of 0.1 micrometer to 3.0 micrometers, more preferably in the range of 0.3 micrometer to 1.5 micrometers, more preferably in the range of 0.4 micrometer to 1.0 micrometer, as determined by scanning electron microscopy.
[0143] 5. The catalyst according to any one of embodiments 1 to 4, wherein the amount of copper contained in the coating is in the range of 2 wt.% to 10 wt.%, calculated as CuO, based on the weight of the zeolite material, preferably in the range of 2.5 wt.% to 8 wt.%, more preferably in the range of 3 wt.% to 7 wt.%, more preferably in the range of 3.5 wt.% to 6 wt.%; the zeolite material contained in the coating preferably contains the copper.
[0144] 6. The catalyst according to any one of embodiments 1 to 5, wherein iron is contained in the zeolite material, wherein the amount of iron contained in the zeolite material is in the range of 0.1 wt% to 1.5 wt%, calculated as Fe2O3, based on the weight of the zeolite material, preferably in the range of 0.15 wt% to 1.25 wt%, more preferably in the range of 0.25 wt% to 1 wt%, more preferably in the range of 0.3 wt% to 0.8 wt%.
[0145] 7. The catalyst according to any one of embodiments 1 to 6, wherein the coating comprises a loading of 0.25 g / in 3 Up to 5g / in 3 In the range of 0.75 g / in 3 Up to 3g / in 3 In the range of 1 g / in 3 Up to 2.5g / in 3 In the range of 1.25 g / in 3 Up to 2.2g / in 3 The zeolite material is within the range of.
[0146] 8. The catalyst according to any one of embodiments 1 to 7, wherein the zeolitic material contained in the coating, preferably the zeolitic material having the framework type CHA, has a relative humidity of 1.5 % at 50 m / s as determined as described in Reference Example 1. 2 / g to 900m 2 / g, preferably within 150 m 2 / g to 700m 2 / g, more preferably within 250 m 2 / g to 650m 2 / g in the range of BET specific surface area.
[0147] 9. The catalyst according to any one of embodiments 1 to 8, wherein 50% to 92% by weight, preferably 65% to 90% by weight, more preferably 70% to 85% by weight of the coating consists of the zeolite material.
[0148] 10. The catalyst according to any one of embodiments 1 to 9, wherein 25 to 65 wt.%, preferably 30 to 60 wt.%, more preferably 40 to 55 wt.%, more preferably 45 to 55 wt.%, of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3.
[0149] 11. The catalyst according to any one of embodiments 1 to 10, wherein 35 to 75 wt.-%, preferably 40 to 70 wt.-%, more preferably 45 to 60 wt.-%, more preferably 45 to 55 wt.-% of the first non-zeolitic oxidic material consists of aluminum calculated as Al2O3.
[0150] 12. The catalyst according to any one of embodiments 1 to 11, wherein the first non-zeolitic oxide material is one or more of an oxide mixture comprising Al and Fe, a mixed oxide comprising Al and Fe, and an Al oxide impregnated with Fe, preferably one or more of a mixed oxide comprising Al and Fe and an Al oxide impregnated with Fe;
[0151] wherein the first non-zeolitic oxidic material has a 2 / g to 300m 2 / g, more preferably in the range of 80m 2 / g to 160m 2 / g in the range of BET specific surface area.
[0152] 13. The catalyst according to any one of embodiments 1 to 12, wherein the coating comprises the first non-zeolitic oxide material in an amount ranging from 5 wt.% to 20 wt.%, preferably ranging from 7 wt.% to 15 wt.%, more preferably ranging from 8 wt.% to 12 wt.%, based on the weight of the zeolitic material.
[0153] 14. The catalyst according to any one of embodiments 1 to 13, wherein 99 to 100 wt. %, preferably 99.5 to 100 wt. %, more preferably 99.9 to 100 wt. % of the first non-zeolitic oxidic material consists of Al, Fe and O.
[0154] 15. The catalyst according to any one of embodiments 1 to 14, wherein 0% to 0.01% by weight, preferably 0% to 0.001% by weight, more preferably 0% to 0.0001% by weight of the first non-zeolitic oxidic material consists of cerium calculated as CeO2.
[0155] 16. The catalyst according to any one of embodiments 1 to 15, wherein the coating further comprises a second non-zeolitic oxidic material, the second non-zeolitic oxidic material preferably comprising one or more of zirconia, alumina, titania, silica, and a mixed oxide comprising two or more of Zr, Al, Ti and Si, more preferably comprising one or more of silica, alumina and zirconia, more preferably comprising one or more of alumina and zirconia, more preferably zirconia;
[0156] Preferably 95 to 100 wt.-%, more preferably 98 to 100 wt.-%, more preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-% of the second non-zeolitic oxidic material comprised in the coating consists of zirconium calculated as ZrO2.
[0157] 17. A catalyst according to any one of embodiments 1 to 16, wherein the coating comprises the following amount of a second non-zeolitic oxide material: based on the weight of the zeolitic material, in the range of 2 wt.% to 40 wt.%, preferably in the range of 2.5 wt.% to 30 wt.%, more preferably in the range of 3 wt.% to 25 wt.%.
[0158] 18. The catalyst according to any one of embodiments 1 to 16, wherein 98 to 100 wt.-%, preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-%, more preferably 99.9 to 100 wt.-% of the coating consists of copper, the zeolitic material optionally comprising iron, the first non-zeolitic oxidic material comprising Fe and Al and preferably the second non-zeolitic oxidic material as defined in embodiment 16 or 17.
[0159] 19. A catalyst according to any one of embodiments 1 to 18, wherein the substrate is made of one or more of cordierite, silicon carbide and aluminum titanate, preferably made of one or more of cordierite and silicon carbide, more preferably made of cordierite or silicon carbide.
[0160] 20. A catalyst according to any one of embodiments 1 to 19, wherein the substrate is a wall-flow filter substrate, wherein the plurality of channels include an inlet channel having an open inlet end and a closed outlet end, and an outlet channel having a closed inlet end and an open outlet end; wherein the wall-flow filter substrate is preferably made of one or more of silicon carbide, aluminum titanate, and more preferably made of silicon carbide.
[0161] 21. The catalyst of embodiment 20, wherein the coating is located within the porous walls of the wall flow filter substrate.
[0162] 22. A catalyst according to embodiments 20 or 21, wherein the coating is uniformly disposed along the axial length of the substrate, or wherein the amount of coating in the middle region of the axial length of the substrate is higher than the amount present at each of the inlet end of the substrate and the outlet end of the substrate, preferably wherein the amount of coating in the middle region of the axial length of the substrate is higher than the amount present at each of the inlet end of the substrate and the outlet end of the substrate.
[0163] 23. The catalyst according to any one of embodiments 20 to 22, wherein the substrate comprises the coating at a loading of 0.5 g / in 3 Up to 3g / in 3 In the range of 0.75 g / in 3 Up to 2.5g / in 3 In the range of 1g / in 3 Up to 2g / in 3 within the range.
[0164] 24. The catalyst according to any one of embodiments 1 to 19, wherein the substrate is a flow-through substrate; wherein the flow-through substrate is preferably made of cordierite.
[0165] 25. The catalyst according to embodiment 24, wherein the coating is located on the surface of the inner wall of the substrate.
[0166] 26. The catalyst of embodiment 24 or 25, wherein the coating is uniformly disposed along the axial length of the substrate.
[0167] 27. The catalyst according to any one of embodiments 24 to 26, wherein the substrate comprises the coating at a loading of 0.75 g / in 3 Up to 5.5g / in 3 In the range of 1.25 g / in 3 Up to 4.5g / in 3 In the range of 2 g / in 3 Up to 4g / in 3 within the range.
[0168] 28. The catalyst according to any one of embodiments 1 to 27, wherein the coating is disposed over 98% to 100% or more of the axial length of the substrate, preferably over 99% to 100% or more.
[0169] 29. The catalyst according to any one of embodiments 1 to 28, consisting of the substrate and the coating.
[0170] 30. A method for preparing a catalyst for selective catalytic reduction of NOx, preferably a catalyst according to any one of embodiments 1 to 29, the method comprising
[0171] (i) preparing a first aqueous mixture comprising water, a copper source and, optionally, a precursor of a second non-zeolitic oxidizing component;
[0172] (ii) mixing the first aqueous mixture obtained according to (i) with water and a zeolite material to obtain a second aqueous mixture, wherein the zeolite material does not contain copper, and wherein the zeolite material optionally comprises iron;
[0173] (iii) mixing a first non-zeolitic oxidic material comprising Al and Fe, wherein at least 25 wt. % of said first non-zeolitic oxidic material consists of iron calculated as Fe2O3, with said second aqueous mixture prepared according to (ii), preferably adding water, to obtain a third aqueous mixture;
[0174] (iv) disposing the third aqueous mixture obtained according to (iii) on a substrate comprising an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels extending therethrough defined by an inner wall of the substrate; and optionally drying the substrate comprising the mixture;
[0175] (v) calcining the substrate obtained in (iv).
[0176] 31. A method according to embodiment 30, wherein the copper source contained in the first aqueous mixture prepared in (i) is selected from copper acetate, copper nitrate, copper sulfate, copper formate, copper oxide and a mixture of two or more thereof, preferably selected from copper acetate, copper oxide and a mixture thereof, more preferably copper oxide, and more preferably CuO.
[0177] 32. The method according to embodiment 30 or 31, wherein the precursor of the second non-zeolitic oxidic component contained in the first aqueous mixture prepared in (i) is a zirconium salt or zirconium oxide, preferably a zirconium salt, more preferably zirconium acetate.
[0178] 33. The method according to any one of embodiments 30 to 32, wherein the first aqueous mixture prepared in (i) comprises copper, calculated as CuO, in an amount in the range of 2 wt.% to 10 wt.%, preferably in the range of 2.5 wt.% to 8 wt.%, more preferably in the range of 3 wt.% to 7 wt.%, more preferably in the range of 3.5 wt.% to 6 wt.%, based on the weight of the zeolitic material contained in the second aqueous mixture prepared in (ii).
[0179] 34. The method according to any one of embodiments 30 to 33, wherein (i) comprises
[0180] (i.1) preparing a mixture comprising water and the copper source, the mixture preferably further comprising an acid, more preferably an organic acid, more preferably acetic acid, wherein the mixture optionally preferably further comprises sucrose;
[0181] (i.2) adding said precursor of said second non-zeolitic oxidation component to said mixture obtained according to (i.1) to obtain said first aqueous mixture.
[0182] 35. The method according to embodiment 34, wherein 90% to 100% by weight, preferably 93% to 99% by weight, more preferably 96% to 99% by weight of the copper source is present in the mixture prepared in (i.1) in an undissolved state.
[0183] 36. A method according to embodiment 35, wherein the copper particles in the mixture according to (i.1) have a Dv90 in the range of 0.1 μm to 15 μm, preferably in the range of 0.5 μm to 10 μm, more preferably in the range of 1 μm to 8 μm, more preferably in the range of 3 μm to 7 μm, and the Dv90 is preferably determined as described in Reference Example 3.
[0184] 37. A method according to any one of embodiments 30 to 36, wherein the second mixture obtained in (ii) has a solid content in the range of 15 wt % to 50 wt %, preferably in the range of 20 wt % to 45 wt %, more preferably in the range of 30 wt % to 40 wt %, based on the weight of the second mixture.
[0185] 38. A method according to any one of embodiments 30 to 37, wherein the zeolite material particles in the second mixture have a Dv50 in the range of 0.5 microns to 5 microns, preferably in the range of 0.75 microns to 3 microns, and the Dv90 is preferably determined as described in Reference Example 3.
[0186] 39. The method according to any one of embodiments 30 to 38, wherein (ii) comprises
[0187] (ii.1) mixing the first aqueous mixture obtained according to (i) with water and a zeolite material, wherein the zeolite material does not contain copper, and wherein the zeolite material optionally comprises iron;
[0188] (ii.2) grinding the obtained mixture (ii.1), preferably until the mixture particles have a Dv90 in the range of 0.5 μm to 8 μm, more preferably in the range of 1 μm to 5 μm, more preferably in the range of 1.5 μm to 4 μm, the Dv90 preferably being determined as described in Reference Example 3, to obtain the third aqueous mixture;
[0189] Wherein more preferably the particles of the mixture have a Dv99 in the range of 1.5 microns to 12 microns, more preferably in the range of 2 microns to 10 microns, more preferably in the range of 3 microns to 7 microns, and the Dv99 is preferably measured as described in Reference Example 3 to obtain the second aqueous mixture.
[0190] 40. A method according to any one of embodiments 30 to 39, wherein the particles of the first non-zeolitic oxidic material mixed with the second aqueous mixture according to (ii) have a Dv90 in the range of 8 microns to 40 microns, preferably in the range of 15 microns to 25 microns, and the Dv90 is preferably determined as described in Reference Example 3.
[0191] 41. A method according to any one of embodiments 30 to 40, wherein the particles of the first non-zeolitic oxidic material mixed with the second aqueous mixture according to (ii) have a Dv99 in the range of 10 microns to 50 microns, preferably in the range of 20 microns to 30 microns, and the Dv99 is preferably determined as described in Reference Example 3.
[0192] 42. The method according to any one of embodiments 30 to 41, wherein the particles of the first non-zeolitic oxidic material mixed with the second aqueous mixture according to (ii) have a particle size of 3
[0193] A Dv50 in the range of 6 microns to 15 microns, preferably in the range of 6 microns to 12 microns, the Dv50 being preferably determined as described in Reference Example 3.
[0194] 43. A method according to any one of embodiments 30 to 42, wherein the mixture prepared in (iii) contains the first non-zeolitic oxide material in an amount ranging from 5 wt.% to 20 wt.%, preferably ranging from 7 wt.% to 15 wt.%, more preferably ranging from 8 wt.% to 12 wt.%, based on the weight of the zeolitic material.
[0195] 44. A method according to any one of embodiments 30 to 43, wherein the third aqueous mixture obtained in (iii) has a solid content in the range of 15 wt% to 50 wt%, preferably in the range of 25 wt% to 48 wt%, and more preferably in the range of 28 wt% to 40 wt%, based on the weight of the third aqueous mixture.
[0196] 45. The process according to any one of embodiments 30 to 44, wherein 98 to 100 wt.-%, preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-%, more preferably 99.9 to 100 wt.-% of the third aqueous mixture obtained according to (iii) consists of water, the zeolitic material optionally comprising iron, the copper source, the first non-zeolitic oxidic material comprising Al and Fe, and more preferably the precursor of the second non-zeolitic oxidic material.
[0197] 46. A method according to any one of embodiments 30 to 45, wherein the mixture according to (iv) is disposed by spraying the third mixture onto the substrate or by immersing the substrate into the mixture, preferably by immersing the substrate into the mixture.
[0198] 47. A method according to any one of embodiments 30 to 46, wherein the third aqueous mixture obtained according to (iii) is arranged according to (iv) within the range of x% of the axial length of the substrate from the inlet end to the outlet end of the substrate or from the outlet end to the inlet end of the substrate, wherein x is in the range of 95 to 100, preferably in the range of 98 to 100, and more preferably in the range of 99 to 100.
[0199] 48. A method according to any one of embodiments 30 to 47, wherein the substrate in (iv) is a flow-through substrate, and the substrate is preferably made of one or more of cordierite, silicon carbide and aluminum titanate, preferably made of one or more of cordierite and silicon carbide, and more preferably made of cordierite.
[0200] 49. The method according to embodiment 48, wherein (iv) comprises
[0201] The third aqueous mixture obtained according to (iii) is arranged on a flow-through substrate at 95% to 100%, preferably 98% to 100%, and more preferably 99% to 100% of the axial length of the substrate from the inlet end toward the outlet end of the substrate or from the outlet end of the substrate toward the inlet end, preferably from the inlet end toward the outlet end; and the substrate containing the mixture is dried.
[0202] 50. A method according to any one of embodiments 30 to 47, wherein the substrate in (iv) is a wall-flow filter substrate, wherein the plurality of channels include an inlet channel having an open inlet end and a closed outlet end, and an outlet channel having a closed inlet end and an open outlet end, and the substrate is preferably made of one or more of cordierite, silicon carbide and aluminum titanate, and more preferably made of one or more of silicon carbide and aluminum titanate.
[0203] 51. The method according to embodiment 50, wherein the arrangement according to (iv) comprises
[0204] (iv.1) placing the first portion of the third aqueous mixture obtained in (iii) on the wall flow filter substrate, the axial length of the substrate from the outlet end of the substrate toward the inlet end being 40% to 85%, preferably 55% to 80%, more preferably 65% to 75%; and drying the substrate containing the first portion of the third aqueous mixture;
[0205] (iv.2) placing the second part of the third aqueous mixture obtained in (iii) on a substrate containing the first part of the third aqueous mixture obtained in (iv.1), wherein the axial length of the substrate from the inlet end toward the outlet end of the substrate is 40% to 85%, preferably 55% to 80%, more preferably 65% to 75%, and optionally drying the substrate containing the first and second parts of the third aqueous mixture.
[0206] 52. The method according to any one of embodiments 30 to 51, wherein the drying according to (iv) is carried out in a gas atmosphere having a temperature in the range of 60°C to 300°C, preferably in the range of 90°C to 150°C, the gas atmosphere preferably comprising oxygen;
[0207] The drying according to (iv) is preferably carried out in a gas atmosphere for a duration in the range of 10 minutes to 4 hours, more preferably in the range of 20 minutes to 2 hours.
[0208] 53. The process according to any one of embodiments 30 to 52, wherein the calcination according to (v) is carried out in a gas atmosphere having a temperature in the range of 300° C. to 900° C., preferably in the range of 400° C. to 650° C., more preferably in the range of 400° C. to 500° C., the gas atmosphere preferably comprising oxygen;
[0209] The calcination according to (v) is preferably carried out in a gas atmosphere for a duration ranging from 0.1 hours to 4 hours, more preferably ranging from 0.5 hours to 2.5 hours.
[0210] 54. The method of any one of embodiments 19 to 53, consisting of (i), (ii), (iii), (iv) and (v).
[0211] 55. A catalyst for selective catalytic reduction of NOx, the catalyst being obtainable by the method according to any one of embodiments 30 to 54 or being obtained by the method according to any one of embodiments 30 to 54.
[0212] 56. An exhaust treatment system for treating exhaust gas leaving a compression ignition engine, preferably a diesel engine, the exhaust treatment system having an upstream end for introducing the exhaust gas flow into the exhaust treatment system, wherein the exhaust treatment system includes a catalyst according to any one of embodiments 1 to 29 and 55, a diesel oxidation catalyst, a selective catalytic reduction catalyst, an ammonia oxidation catalyst, one or more, a NOx trap and a particulate filter.
[0213] 57. The system of embodiment 56, comprising a diesel oxidation catalyst, wherein the catalyst of any one of embodiments 1 to 29 and 55 is located downstream of the diesel oxidation catalyst.
[0214] 58. The system of embodiment 56 or 57, comprising a diesel oxidation catalyst, a selective catalytic reduction catalyst on a filter, a catalyst according to any one of embodiments 1 to 29 and 55, wherein the diesel oxidation catalyst is upstream of the selective catalytic reduction catalyst on a filter (SCRoF), and the catalyst according to any one of embodiments 1 to 29 and 55 is downstream of the SCRoF catalyst;
[0215] Wherein the system further comprises a selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the catalyst according to any one of embodiments 1 to 29 and 55.
[0216] 59. The system of embodiment 56 or 57, comprising a diesel oxidation catalyst, a selective catalytic reduction catalyst, a catalyst according to any one of embodiments 1 to 29 and 55, wherein the diesel oxidation catalyst is upstream of the selective catalytic reduction (SCR) catalyst, and the catalyst according to any one of embodiments 1 to 29 and 55 is downstream of the SCR catalyst;
[0217] Wherein the system further comprises a selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the catalyst according to any one of embodiments 1 to 29 and 55.
[0218] 60. The system of embodiment 56 or 57, comprising a diesel oxidation catalyst, a selective catalytic reduction catalyst, a catalyst according to any one of embodiments 1 to 29 and 55, wherein the diesel oxidation catalyst is upstream of the catalyst according to any one of embodiments 1 to 29 and 55, and the selective catalytic reduction (SCR) catalyst is downstream of the catalyst according to any one of embodiments 1 to 29 and 55;
[0219] The system further comprises an additional selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the SCR catalyst.
[0220] 61. The system of embodiment 56 or 57, comprising a diesel oxidation catalyst, a selective catalytic reduction catalyst on a filter (SCRoF), a catalyst according to any one of embodiments 1 to 29 and 55, wherein the diesel oxidation catalyst is upstream of the catalyst according to any one of embodiments 1 to 29 and 55, and the SCRoF catalyst is downstream of the catalyst according to any one of embodiments 1 to 29 and 55;
[0221] The system further comprises a selective catalytic reduction catalyst or an ammonia oxidation catalyst downstream of the SCRoF catalyst.
[0222] 62. Use of the catalyst according to any one of embodiments 1 to 29 and 55 for the selective catalytic reduction of NOx.
[0223] 63. A method for selective catalytic reduction of NOx, the method comprising
[0224] (1) providing an exhaust gas flow, preferably away from a diesel engine;
[0225] (2) The exhaust gas flow provided in (1) is brought into contact with the catalyst for selective catalytic reduction of NOx according to any one of Embodiments 1 to 29 and 55.
[0226] Furthermore, it should be expressly noted that the above set of embodiments represents a properly structured portion of a general description of preferred aspects of the invention, and therefore properly supports but does not represent the claims of the invention.
[0227] Systems according to the invention are listed in the table below.
[0228] system Catalyst 1 Catalyst 2 Catalyst 3 Catalyst 4 1 DOC SCRoF Calculated as SCR SCR or AMOx 2 DOC SCR Calculated as SCRoF SCR or AMOx 3 DOC Calculated as SCRoF SCR SCR or AMOx 4 DOC Calculated as SCR SCRoF SCR or AMOx
[0229] Catalyst 1 is located upstream of catalyst 2, catalyst 2 is located upstream of catalyst 3, and catalyst 3 is located upstream of catalyst 4. In the above table, "calculated" means a catalyst according to the present invention. In addition, "DOC" means a diesel oxidation catalyst, "SCR" means a selective catalytic reduction catalyst, and "AMOx" means an ammonia oxidation catalyst. "Calculated as SCR" means that the catalyst according to the present invention is an SCR catalyst on a flow-through substrate and "calculated as SCRoF" means that the catalyst according to the present invention is an SCR catalyst on a wall-flow filter substrate.
[0230] In the context of the present invention, the term "SCR" means a selective catalytic reduction catalyst and the term "SCRoF" means a selective catalytic reduction catalyst on a wall flow filter substrate.
[0231] In the context of the present invention, it is preferred that the catalyst of the present invention is located downstream of a diesel engine.
[0232] Furthermore, in the context of the present invention, the term "loading amount of a given component / coating" (in g / in 3 or g / ft 3 ) refers to the mass of the component / coating per unit volume of substrate, where the volume of the substrate is defined by the cross-section of the substrate multiplied by the axial length of the substrate over which the component / coating is present. For example, if reference is made to extending x% over the axial length of the substrate and having X g / in 3 The loading of the first coating layer is the loading of the first coating layer, then the loading will refer to the volume of the entire substrate (in 3 X grams of first coating for every x% of (in units).
[0233] Furthermore, in the context of the present invention, the term "based on the weight of the zeolitic material" refers to the weight of the zeolitic material only, meaning without copper.
[0234] Furthermore, in the context of the present invention, the term "X is one or more of A, B, and C", where X is a given feature and each of A, B, and C represents a specific implementation of the feature, should be understood to disclose that X is A, or B, or C, or A and B, or A and C, or B and C, or A and B and C. In this regard, it should be noted that a skilled person is able to convert the above abstract terms into concrete examples, such as where X is a chemical element and A, B, and C are specific elements such as Li, Na, and K, or X is a temperature and A, B, and C are specific temperatures such as 10°C, 20°C, and 30°C. In this regard, it should also be noted that the skilled person is able to expand the above terms to less specific implementations of the features, such as “X is one or more of A and B” discloses that X is A, or B, or A and B, or to more specific implementations of the features, such as “X is one or more of A, B, C, and D” discloses that X is one or more of A, or B, or C, or D, or A and B, or A and C, or A and D, or B and C, or B and D, or C and D, or A and B and C, or A and B and D, or B and C and D.
[0235] The present invention is further illustrated by the following examples. Example
[0236] Measurement of BET specific surface area and micropore surface area (ZSA) with reference to Example 1
[0237] The BET specific surface area and ZSA are determined according to DIN 66131 or DIN-ISO 9277 using liquid nitrogen.
[0238] Reference Example 2 Measurement of Average Porosity and Average Pore Size of Porous Wall Flow Substrate
[0239] The average porosity of the porous wall-flow substrate is determined by mercury porosimetry using mercury intrusion porosimetry according to DIN 66133 and ISO 15901-1.
[0240] Reference Example 3 Determination of volume-based particle size distribution
[0241] The particle size distribution was determined by static light scattering using Sympatec HELOS (3200) & QUIXEL equipment, where the optical concentration of the samples was in the range of 6% to 10%.
[0242] Reference Example 4: Preparation of Fe-CHA
[0243] H-chabazite (having a Dv50 of 1.548 μm, a SiO2:Al2O3 molar ratio of 15.7:1, and a 2 / g BET specific surface area and 570m 2 / g of micropore surface area (ZSA)) was impregnated with iron (iron source: Fe-(III)-nitrate-9-hydrate) via incipient wetness impregnation so that the amount of iron calculated as Fe2O3 was 0.6 wt% Fe based on the weight of chabazite.
[0244] Comparative Example 1 SCR catalyst not according to the present invention
[0245] CuO powder having a Dv50 of 1.1 microns and a Dv90 of 5.8 microns was added to water. The amount of CuO was calculated so that the total amount of copper in the calcined coating calculated as CuO was 5 wt % based on the weight of the chabazite. Acetic acid and an aqueous zirconium acetate solution were added to the CuO-containing mixture to form a slurry. The amount of acetic acid was calculated to be 1.7 wt % of the chabazite, and the amount of zirconium acetate was calculated so that the amount of zirconium oxide (calculated as ZrO2) in the coating was 5 wt % based on the weight of the chabazite. H-chabazite (Dv50 of 1.548 microns, SiO2:Al2O3 of 15.7:1, BET surface area of 590 m 2 / g, and the micropore surface area ZSA is 570m 2 / g) was added to the copper-containing slurry to form a mixture having a solid content of 41 wt % based on the weight of the mixture. The resulting slurry was ground using a continuous grinding device to a particle Dv50 value of about 1.35 microns, a particle Dv90 value of about 2.5 microns, and a particle Dv90 value of about 7 microns.
[0246] Alumina powder (BET specific surface area 185m 2 80 wt% Al2O3 and 20 wt% SiO2 (80 wt% Al2O3 and 20 wt% SiO2 with 0.1% MgO / g, Dv50 of 6.3 microns and Dv90 of 16.3 microns) were added to the Cu / CHA containing slurry. The amount of alumina + silica was calculated so that the amount of calcined alumina + silica was 5 wt% based on the weight of calcined chabazite in the final catalyst. Water was added to the resulting mixture to obtain a mixture with a solid content of 42 wt% based on the weight of the mixture.
[0247] A porous uncoated flow-through substrate cordierite (volume: 2 L, 400 cpsi, 3.5 mil wall thickness, diameter: 5.66 inches x length: 5 inches) was coated from the inlet end to the outlet end with a final slurry exceeding 100% of the axial length of the substrate. To do this, the substrate was immersed in the final slurry from the inlet end until the slurry reached the top of the substrate. In addition, the coated substrate was dried at 140°C for 30 minutes and calcined at 450°C for 1 hour. The final coating loading in the catalyst after calcination was 2.75 g / in 3 , including about 2.39 g / in based on the weight of chabazite 3 Chabazite, 0.12g / in 3Zirconia, 0.12g / in 3 of aluminum oxide and 5 wt.% of Cu.
[0248] Example 1 CR catalyst according to the present invention
[0249] The catalyst of Example 1 was prepared as the catalyst of Comparative Example 1, except that Fe-chabazite prepared according to Reference Example 4 (Fe content: 0.6 wt %, calculated as Fe2O3 based on the weight of chabazite, Dv50 of 1.548 μm, SiO2:Al2O3 of 15.7:1, BET specific surface area of 590 m 2 / g, and the micropore surface area ZSA is 570m 2 / g) instead of H-type chabazite, alumina powder (80 wt% Al2O3 and 20 wt% SiO2, with 185 m 2 / g, a BET specific surface area of 6.3 μm, a Dv50 of 16.3 μm and a Dv90 of 16.3 μm) were replaced by a powder of a non-zeolitic oxide material containing Fe and Al (50 wt% Fe2O3 and 50 wt% Al2O3, the BET specific surface area of which was 112.85 m 2 / g, Dv50 is 9.6 microns, Dv90 is 20.5 microns, and Dv99 is 28.2 microns) and the amount of alumina + iron is calculated so that the amount of alumina + iron after calcination is 10 weight % based on the weight of chabazite after calcination.
[0250] The final coating loading in the catalyst after calcination was 2.4 g / in 3 , including about 2.0g / in 3 Chabazite, 0.1g / in 3 Zirconia, 0.2g / in 3 % of non-zeolitic oxide material, 0.6 wt% Fe calculated as Fe2O3 based on the weight of chabazite, and 5 wt% Cu calculated as CuO based on the weight of chabazite. The other components are burned out and do not contribute to the final coating loading.
[0251] Example 2 Testing of the performance of the catalysts prepared in Comparative Example 1 and Example 1
[0252] Prior to testing, the catalysts of Comparative Example 1 and Example 1 were hydrothermally aged in an oven with 10% H2O and 20% O2 at 800°C in N2 for 16 hours. Engine bench testing was performed under steady-state conditions to measure DeNOx activity and N2O formation. The results are shown in Figure 1 and Figure 2 middle.
[0253] Table 1 Engine bench conditions
[0254] Temperature [℃] <![CDATA[Volume flow rate [m 3 / h]]]> NOx engine emissions [ppm] NSR 200 144 273 1.5 230 165 381 1.5 600 112 351 2 650 118 410 2
[0255] As from Figure 1 As can be seen from the figure, in terms of NOx conversion, both catalysts have a good NOx conversion rate at low temperatures and at high temperatures of about 80% to 100%. Figure 2 As can be seen in the Figures, although the results are similar at low temperatures (200°C and 230°C), the SCR catalyst of the present invention allows to reduce the formation of N2O by more than 50% compared to the catalyst of Comparative Example 1, while maintaining similar NOx conversion rates of about 90% to 98% at high temperatures, i.e. at 601°C and 650°C.
[0256] The catalyst of the invention comprising iron in combination with alumina in its coating thus allows a significant reduction in the formation of N2O while maintaining very good NOx conversions at high temperatures.
[0257] Comparative Example 2 SCR (SCRoF) catalyst on a filter not according to the invention
[0258] CuO powder having a Dv50 of 1.1 microns and a Dv90 of 5.8 microns was added to water. The amount of CuO was calculated so that the total amount of copper calculated as CuO in the calcined coating was 4.15 wt % based on the weight of the chabazite. Sucrose was further added to the Cu mixture, and the amount of sucrose was calculated so that it was 4.15 wt % based on the weight of the chabazite. Acetic acid was added to the obtained slurry. The amount of acetic acid was calculated so that it was 1.7 wt % based on the weight of the chabazite. The resulting slurry had a solid content of 5 wt % based on the weight of the slurry. An aqueous solution of zirconium acetate was added to the mixture containing CuO to form a slurry. The amount of zirconium acetate was calculated so that the amount of zirconium oxide calculated as ZrO2 in the coating was 20 wt % based on the weight of the chabazite. H-chabazite (Dv50 of 1.548 microns, SiO2:Al2O3 of 15.7:1, BET specific surface area of 590 m 2 / g, and a micropore surface area (ZSA) of 570 m 2 / g) was added to a copper-containing slurry having a solid content of 37 wt % based on the weight of the mixture. The resulting slurry was ground using a continuous grinding device to a particle Dv99 value of about 9 microns, a particle Dv90 value of about 2.5 microns, and a particle Dv50 value of about 1.35 microns.
[0259] Alumina powder (BET specific surface area 178m 2100 wt% Al2O3 (100 wt% Al2O3 with 0.1% Al2O3 / g, Dv50 of 2.6 microns, Dv90 of about 5.3 microns and Dv99 of about 8.5 microns) was added to the Cu / CHA containing slurry. The amount of alumina was calculated so that the amount of calcined alumina + silica was 10 wt% based on the weight of calcined chabazite in the final catalyst. Water was added to the resulting mixture to obtain a mixture with a solid content of 37 wt% based on the weight of the mixture.
[0260] In the optimized design, a porous uncoated wall-flow filter substrate silicon carbide (volume: 3.4 L, average porosity of 59%, average pore size of 17.5 microns and 350 cpsi and 12 mil wall thickness, diameter: 6.43 inches × length: 6.39 inches) was coated twice with the obtained mixture, wherein the first coating covered 70% of the substrate length from the outlet end to the inlet end, and the second coating covered 70% of the substrate length from the inlet end to the outlet end, forming a single coating extending along the entire length of the substrate. To this end, the substrate was immersed in the corresponding slurry starting from the outlet end until the slurry reached 70% of the substrate length. After immersion from the outlet end, a pressure pulse was applied from the inlet end to blow out excess slurry. In addition, the substrate was immersed in the corresponding slurry starting from the inlet end until the slurry reached 70% of the substrate length. After immersion from the inlet end, a pressure pulse was applied from the outlet end to blow out excess slurry. In addition, the coated substrate was dried at 140°C for 30 minutes and calcined at 450°C for 1 hour. The final coating loading in the calcined catalyst was 1.75 g / in 3 , including about 1.31 g / in based on the weight of chabazite 3 Chabazite, 0.26g / in 3 Zirconia, 0.13g / in 3 of aluminum oxide and 4.15 wt. % of Cu.
[0261] Example 3 SCR (SCRoF) catalyst on filter according to the present invention
[0262] The catalyst of Example 3 was prepared as the catalyst of Comparative Example 2, except that Fe-chabazite (Fe content: 0.6 wt %, calculated as Fe2O3 based on the weight of chabazite, Dv50 of 1.548 μm, SiO2:Al2O3 of 15.7:1, BET specific surface area of 590 m2) prepared as described in Reference Example 4 was used. 2 / g, and the micropore surface area ZSA is 570m 2 / g) instead of H-type chabazite, and the alumina powder (Al2O3 100 wt%) was replaced by a powder of a non-zeolitic oxide material containing Fe and Al (Fe2O3 50 wt% and Al2O3 50 wt%, the material having a Dv50 of 10.15 μm and a Dv90 of 100.13 μm).
[0263] The final coating loading in the calcined catalyst was 1.75 g / in 3 , including about 1.31g / in 3 Chabazite, 0.26g / in 3 Zirconia, 0.13g / in 3 % of non-zeolitic oxide material, 0.6 wt% Fe calculated as Fe2O3 based on the weight of chabazite, and 4.15 wt% Cu calculated as CuO based on the weight of chabazite. The other components are burned out and do not contribute to the final coating loading.
[0264] Comparative Example 3 SCR (SCRoF) catalyst outlet slurry on a filter not according to the invention :
[0265] H-chabazite (Dv50 of 1.548 μm, SiO2:Al2O3 of 15.7:1, BET specific surface area of 590 m 2 / g, and a micropore surface area (ZSA) of 570 m 2 / g) was impregnated with Fe (0.6 wt% Fe, calculated as Fe2O3 based on the weight of chabazite, Fe source: Fe-(III)-nitrate-9 hydrate). Separately, CuO powder with a Dv50 of 1.1 microns and a Dv90 of 5.8 microns was added to water. The amount of CuO was calculated so that the total amount of copper calculated as CuO in the calcined coating was 3.5 wt% based on the weight of the chabazite. Sucrose was further added to the Cu mixture, and the amount of sucrose was calculated so that it was 3.5 wt% based on the weight of the chabazite. Acetic acid was then added to the obtained slurry. The amount of acetic acid was calculated so that it was 1.7 wt% based on the weight of the chabazite. The resulting slurry had a solid content of 5 wt% based on the weight of the slurry. An aqueous zirconium acetate solution was added to the CuO-containing mixture to form a slurry. The amount of zirconium acetate was calculated so that the amount of zirconium oxide calculated as ZrO2 in the coating was 20 wt% based on the weight of the chabazite. In addition, the Fe chabazite obtained previously was added to water and mixed with the copper-containing slurry. The resulting slurry was ground using a continuous grinding device so that the Dv99 value of the particles was about 9 microns, the Dv90 value of the particles was about 2.5 microns, and the Dv50 value of the particles was about 1.35 microns.
[0266] Alumina powder (BET specific surface area 178m 2 100 wt% Al2O3 (100 wt% Al2O3 having a Dv50 of 2.6 microns, a Dv90 of about 5.3 microns, and a Dv99 of about 8.5 microns) was added to the slurry containing chabazite. The amount of alumina was calculated so that the amount of calcined alumina was 10 wt% based on the weight of the calcined chabazite. Water was added to the resulting mixture to obtain a mixture with a solid content of 37 wt% based on the weight of the mixture.
[0267] Inlet slurry :
[0268] Zirconium acetate was used to disperse Fe BEA zeolite (Fe content based on the weight of BEA was 6.5 wt%, calculated as Fe2O3, Dv50 was 2.1 μm, SiO2:Al2O3 was 9.6:1, and the BET specific surface area was 476 m 2 / g). The amount of zirconium acetate was calculated so that the amount of zirconium oxide in the coating calculated as ZrO2 was 20% by weight based on the weight of the BEA zeolite. The resulting mixture was ground using a continuous grinding apparatus so that the Dv99 value of the particles was about 9 microns, the Dv90 value of the particles was about 3 microns, and the Dv50 value of the particles was about 1.5 microns. In addition, alumina powder (BET specific surface area of 178 m 2 100 wt% Al2O3 (100 wt% Al2O3 with 0.1% MgO3 / g, Dv50 of 2.6 microns, Dv90 of about 5.3 microns and Dv99 of about 8.5 microns) was added to the slurry containing BEA. The amount of alumina was calculated so that the amount of alumina after calcination was 10 wt% based on the weight of BEA after calcination. Water was added to the resulting mixture to obtain a mixture with a solid content of 37 wt% based on the weight of the mixture.
[0269] In the optimized design, a porous uncoated wall flow filter substrate, silicon carbide, (volume: 3.4 L, average porosity of 59%, average pore size of 17.5 microns and 350 cpsi and 12 mil wall thickness, diameter: 6.43 inches × length: 6.39 inches) was coated twice, wherein a first coating was applied from the outlet end to the inlet end over 80% of the substrate length using the outlet slurry, followed by a second coating from the inlet end to the outlet end also over 80% of the substrate length using the inlet slurry. To this end, the substrate was immersed in the corresponding slurry starting from the outlet end until the slurry reached 80% of the substrate length. After immersion from the outlet end, a pressure pulse was applied from the inlet end to blow out excess slurry. In addition, the substrate was immersed in the corresponding slurry starting from the inlet end until the slurry reached 80% of the substrate length. After immersion from the inlet end, a pressure pulse was applied from the outlet end to blow out excess slurry. In addition, the coated substrate was dried at 140°C for 30 minutes and calcined at 450°C for 1 hour.
[0270] The final coating loading in the catalyst after calcination was 1.76 g / in 3 , including about 1.6g / in 3 Chabazite-based coating and 0.6 g / in 3 Fe-BEA based coating.
[0271] Example 4 Testing of the performance of the catalysts prepared by Comparative Examples 2 and 3 and Example 3
[0272] Prior to testing, the catalysts of Comparative Examples 2 and 3 and Example 3 were hydrothermally aged for 16 hours in an oven at 850°C at a high flow rate of 25 L, 2.422 ml / min H2O and 20% O2 (residual N2). Engine bench testing was performed under steady-state conditions (Daimler-OM651, 2.2 L, 4Zyl.150 kW), and DeNOx activity as well as N2O formation were measured. The results are shown in Figures 3 to 6 middle.
[0273] Table 2 Engine bench conditions
[0274] Temperature [℃] <![CDATA[Volume flow rate [m 3 / h]]]> NOx engine emissions [ppm] NSR 195 137 244 1.50 231 160 356 1.50 598 112 368 2.00 650 119 416 2.00
[0275] As from Figure 3 It can be seen that the catalyst according to the present invention exhibits good NOx conversion at both low and high temperatures, i.e., about 95% at 231°C, 90% at 599°C, and about 75% at 650°C, which is very similar to the NOx conversion obtained with the catalyst of Comparative Example 2. Figure 4 It can be seen that the SCR catalyst of the present invention allows reducing N2O formation by up to about 50% in a very wide temperature range of 195°C to 650°C compared to the catalyst of Comparative Example 2. Moreover, compared to the catalyst of Comparative Example 3, the catalyst of Example 2 according to the present invention shows the best compromise in terms of the balance between good NOx conversion and acceptable N2O formation. In fact, the catalyst of Example 2 shows an improved NOx conversion of about 20%-30% compared to the catalyst of the Comparative Example. In Example 3, the N2O formation of the catalyst of Example 2 increases by only 0.5% compared to the catalyst of Comparative Example 3 at low temperatures. This is due to the fact that the catalyst of Example 2 shows an improved NOx conversion of about 20%-30% compared to the catalyst of Comparative Example 3. Figure 5 and Figure 6 Shown.
[0276] The catalyst of the invention comprising iron in combination with alumina in its coating thus allows a significant reduction in the formation of N2O while maintaining very good NOx conversions at high temperatures.
[0277] Comparative Example 4 SCR (SCRoF) catalyst on a filter not according to the invention
[0278] The catalyst of Comparative Example 4 was prepared as the catalyst of Comparative Example 2, except that H-CHA was replaced by Fe-CHA, wherein CHA had a Dv50 of 1.548 microns, a SiO2:Al2O3 ratio of 15.7:1, and a 2 / g BET specific surface area and 570m 2 / g micropore surface area ZSA, Fe content of 0.6 wt% based on the weight of chabazite calculated as Fe2O3, Fe-CHA prepared according to Reference Example 4 herein. The final coating loading in the catalyst after calcination was 1.75 g / in3 , including about 1.31g / in 3 Chabazite, 0.26g / in 3 Zirconia, 0.13g / in 3 % of alumina, 0.6 wt. % of Fe calculated as Fe2O3 based on the weight of chabazite, and 4.15 wt. % of Cu calculated as CuO based on the weight of chabazite.
[0279] Comparison of the performance of Comparative Examples 2 and 4 with reference to Example 5
[0280] Before testing, the catalysts of Comparative Examples 2 and 4 were hydrothermally aged in an oven at 850°C for 16 hours at 25L high flow rate, 20% O2, 2.422ml / min H2O (residual N2). Engine bench testing was performed under steady-state conditions (Daimler-OM651, 2.2L, 4Zyl.150kW) and DeNOx activity as well as N2O formation were measured. The results are shown in Figures 7 and 8 middle.
[0281] Table 3 Engine bench conditions
[0282] Temperature [℃] <![CDATA[Volumetric flow rate [m 3 / h]]]> NOx engine emissions [ppm] NSR 200 133 269 1.5 230 152 334 1.5 350 159 303 1.2 600 106 373 2 650 114 419 2
[0283] As from Figure 7 It can be seen that the NOx conversion performance of the two comparative examples is approximately the same. Figure 8 It can be seen that, compared with the catalyst of Comparative Example 2 using Cu-CHA (starting zeolite is H-CHA), the catalyst of Comparative Example 4 using Cu / Fe-CHA (starting zeolite is CHA impregnated with Fe), nitrous oxide formation is reduced by up to more than 0.5%. Therefore, it can be inferred from the described embodiment that, compared with using Cu-CHA in such catalysts, using Fe / Cu-CHA in catalysts can reduce the formation of nitrous oxide. However, the nitrous oxide formation obtained with the catalyst of Comparative Example 4 is higher than the nitrous oxide formation obtained with the catalyst of Example 1 according to the present invention. In fact, using the catalyst of the present invention, the obvious reduction of nitrous oxide can be observed at low temperatures and at high temperatures, wherein, compared with Comparative Example 2, nitrous oxide is reduced by about 2% at 650°C.
[0284] It is thus clear from the experimental part of the present invention that a catalyst according to the invention comprising iron in combination with aluminium oxide in its coating allows a significant reduction in the formation of N2O while maintaining a very good NOx conversion.
[0285] Example 5 SCR (SCRoF) catalyst on filter according to the present invention
[0286] The catalyst of Example 5 was prepared as the catalyst of Comparative Example 2, except that
[0287] -Dv50 is 1 micron, SiO2:Al2O3 is 18:1, BET specific surface area is 550m 2 / g and micropore surface area ZSA is 520m 2 / g of H-type chabazite instead of H-type chabazite),
[0288] - Alumina powder (80 wt% Al2O3 and 20 wt% SiO2, BET surface area 185 m 2 / g, Dv50 of 6.3 μm and Dv90 of 16.3 μm) was mixed with a non-zeolitic oxide material powder containing Fe and Al (50 wt% of Fe2O3 and 50 wt% of Al2O3, the BET specific surface area of the material being 112.85 m 2 / g, Dv50 is 9.6 microns, Dv90 is 20.5 microns, Dv99 is 28.2 microns); and
[0289] -Replace the porous uncoated wall flow filter substrate silicon carbide with a volume of 0.428L, an average porosity of 59%, an average pore size of 17.5 microns and 350 cpsi and a wall thickness of 12 mils, diameter: 6.43 inches x length: 6.39 inches with a porous uncoated wall flow filter substrate silicon carbide with a volume of 3.4L, an average porosity of 59%, an average pore size of 17.5 microns and 350 cpsi and a wall thickness of 12 mils, diameter: 2.3 inches x length: 6.39 inches.
[0290] The final coating loading in the catalyst after calcination was 1.97 g / in 3 , including about 1.469g / in 3 Chabazite, 0.29g / in 3 Zirconia, 0.15g / in 3 of non-zeolitic oxide material containing Fe and Al and 4.15 wt. % copper, calculated as CuO based on the weight of chabazite. The other ingredients were burned out and did not contribute to the final coating loading.
[0291] Comparative Example 5 SCR (SCRoF) catalyst on a filter not according to the invention
[0292] The catalyst of Comparative Example 5 was prepared as the catalyst of Comparative Example 2, except that H-chabazite was used instead of H-chabazite, and had a Dv50 of 1 micron, a SiO2:Al2O3 ratio of 18:1, and a 550 m 2 / g BET specific surface area and 520m 2 / g of micropore surface area ZSA), and a porous uncoated wall flow filter substrate silicon carbide, volume: 3.4L, average porosity 59%, average pore size 17.5 microns and 350 cpsi and 12 mil wall thickness, diameter: 6.43 inches × length: 6.39 inches, was replaced by a porous uncoated wall flow filter substrate silicon carbide, volume: 0.428L, average porosity 59%, average pore size 17.5 microns and 350 cpsi and 12 mil wall thickness, diameter: 2.3 inches × length: 6.39 inches.
[0293] The final coating loading in the catalyst after calcination was 1.97 g / in 3 , including about 1.469g / in 3 Chabazite, 0.29g / in 3 Zirconia, 0.15g / in 3 of non-zeolitic oxide material containing Fe and Al and 4.15 wt. % copper, calculated as CuO based on the weight of chabazite. The other ingredients were burned out and did not contribute to the final coating loading.
[0294] Example 6 Testing of the performance of the catalysts prepared in Comparative Example 5 and Example 5
[0295] The catalysts of Comparative Example 5 and Example 5 were hydrothermally aged for 16 hours in an oven at 850°C with 10% H2O and 20% O2 (balance N2) before testing. The engine bench test was carried out under steady-state conditions (Daimler-OM651, 2.2L, 4Zyl.150kW). DeNOx activity and N2O formation were measured. The results are shown in Figures 9 and 10 middle.
[0296] Table 4 Engine bench conditions
[0297] Temperature [℃] <![CDATA[Volume flow rate [m 3 / h]]]> NOx engine emissions [ppm] NSR 578 10 470 4 630 10 380 4
[0298] As from Fig. 9 It can be seen that the catalyst according to the present invention (Example 5) shows good NOx conversion at high temperatures, i.e. about 95% at 578°C and about 80% at 630°C, which is very similar to the NOx conversion obtained with the catalyst of Comparative Example 5. Fig.10 As can be seen, the SCR catalyst of the present invention allows a reduction of more than 7% of N2O formation at 578° C. and up to 16% at 630° C. compared to the catalyst of Comparative Example 5. In addition, compared to the catalyst of Comparative Example 5, the catalyst of Example 5 according to the present invention shows the best compromise in terms of the balance between good NOx conversion and acceptable N2O formation.
[0299] The catalyst of the invention comprising iron in combination with alumina in its coating thus allows a significant reduction in the formation of N2O while maintaining very good NOx conversions at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0300] Figure 1 The NOx conversion rates obtained by the catalysts of Example 1 and Comparative Example 1 at different temperatures are shown.
[0301] Figure 2 The N2O formed when the catalysts of Example 1 and Comparative Example 1 are used at different temperatures is shown. The calculation formula for relative N2O is relative N2O [%] = N2O [ppm] / (NOx engine output [ppm] * NOx conversion rate [%] / 100) * 100
[0302] Figure 3 The NOx conversion rates obtained by the catalysts of Example 3 and Comparative Example 2 in a wide temperature range (195° C. to 650° C.) are shown.
[0303] Figure 4 The N2O formed when the catalysts of Example 3 and Comparative Example 2 are used in a wide temperature range (195°C to 650°C) is shown. The calculation formula of relative N2O is relative N2O [%] = N2O [ppm] / (NOx engine output [ppm] * NOx conversion rate [%] / 100) * 100
[0304] Figure 5 The NOx conversion rates obtained at low temperatures (198° C. and 231° C.) for the catalysts of Example 3 and Comparative Examples 2 and 3 are shown.
[0305] Figure 6 The N2O formed when the catalysts of Example 3 and Comparative Examples 2 and 3 were used at low temperatures (198°C and 231°C) is shown. The calculation formula for relative N2O is relative N2O [%] = N2O [ppm] / (NOx engine output [ppm] * NOx conversion rate [%] / 100) * 100
[0306] Figure 7 The NOx conversion rates obtained with the catalysts of Comparative Examples 2 and 4 are shown.
[0307] Figure 8 The N2O formed when the catalysts of Comparative Examples 2 and 4 were used is shown. The calculation formula of relative N2O is relative N2O [%] = N2O [ppm] / (NOx engine output [ppm] * NOx conversion rate [%] / 100) * 100
[0308] Fig. 9 The NOx conversion rates obtained with the catalysts of Comparative Example 5 and Example 5 are shown.
[0309] Fig.10 The relative N2O advantage formed when using the catalyst of Example 5 compared to the catalyst of Comparative Example 5 is shown.
[0310] Citations
[0311] -US 9 242 238 B2
[0312] -US 9 352 307 B2
[0313] -US 9 999 877 B2
Claims
1. A catalyst for selective catalytic reduction of NOx, the catalyst comprising a substrate having an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate extending therethrough; A coating comprising a zeolitic material, copper and a first non-zeolitic oxidic material comprising iron and aluminum, wherein at least 25 wt. % of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3.
2. The catalyst according to claim 1, wherein the zeolite material contained in the coating layer has a framework type selected from the group consisting of CHA, AEI, RTH, LEV, DDR, KFI, ERI, AFX, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of CHA, AEI, RTH, AFX, a mixture of two or more thereof, and a mixed type of two or more thereof, more preferably selected from the group consisting of CHA and AEI, wherein the zeolite material contained in the coating layer more preferably has a framework type CHA.
3. The catalyst according to claim 1 or 2, wherein the amount of copper contained in the coating is in the range of 2 wt. % to 10 wt. %, calculated as CuO, based on the weight of the zeolite material, preferably in the range of 2.5 wt. % to 8 wt. %, more preferably in the range of 3 wt. % to 7 wt. %, more preferably in the range of 3.5 wt. % to 6 wt. %; the zeolite material contained in the coating preferably contains copper.
4. The catalyst according to any one of claims 1 to 3, wherein the zeolite material comprises iron, wherein the amount of iron contained in the zeolite material, calculated as Fe2O3, based on the weight of the zeolite material, is in the range of 0.1 wt.% to 1.5 wt.%, preferably in the range of 0.15 wt.% to 1.25 wt.%, more preferably in the range of 0.25 wt.% to 1 wt.%, more preferably in the range of 0.3 wt.% to 0.8 wt.%.
5. The catalyst according to any one of claims 1 to 4, wherein 25 to 65 wt.-%, preferably 30 to 60 wt.-%, more preferably 40 to 55 wt.-%, more preferably 45 to 55 wt.-% of the first non-zeolitic oxidic material consists of iron calculated as Fe2O3.
6. The catalyst according to any one of claims 1 to 5, wherein the coating comprises the first non-zeolitic oxidic material in an amount in the range of 5 wt.% to 20 wt.%, preferably in the range of 7 wt.% to 15 wt.%, more preferably in the range of 8 wt.% to 12 wt.%, based on the weight of the zeolitic material.
7. The catalyst according to any one of claims 1 to 6, wherein 99 to 100 wt.-%, preferably 99.5 to 100 wt.-%, more preferably 99.9 to 100 wt.-% of the first non-zeolitic oxidic material consists of Al, Fe and O.
8. The catalyst according to any one of claims 1 to 7, wherein in the catalyst, the weight ratio of the zeolitic material relative to the first non-zeolitic oxidic material is in the range of 4.6:1 to 10:1, more preferably in the range of 6:1 to 9.3:1, more preferably in the range of 7:1 to 8.75:
1.
9. The catalyst according to any one of claims 1 to 8, wherein the coating further comprises a second non-zeolitic oxidic material, the second non-zeolitic oxidic material preferably comprising one or more of zirconium oxide, aluminum oxide, titanium dioxide, silicon dioxide, and a Zr, Al, Ti and Si, more preferably comprising one or more of silicon dioxide, aluminum oxide and zirconium oxide, more preferably comprising one or more of aluminum oxide and zirconium oxide, more preferably zirconium oxide; Preferably 95 to 100 wt.-%, more preferably 98 to 100 wt.-%, more preferably 99 to 100 wt.-%, more preferably 99.5 to 100 wt.-% of the second non-zeolitic oxidic material comprised in the coating consists of zirconium calculated as ZrO2.
10. A method for preparing a catalyst for selective catalytic reduction of NOx, preferably a catalyst according to any one of claims 1 to 9, the method comprising (i) preparing a first aqueous mixture comprising water, a copper source and preferably a precursor of a second non-zeolitic oxidizing component; (ii) mixing the first aqueous mixture obtained according to (i) with water and a zeolite material to obtain a second aqueous mixture, wherein the zeolite material does not contain copper, and wherein the zeolite material optionally comprises iron; (iii) mixing a first non-zeolitic oxidic material comprising Al and Fe, wherein at least 25 wt. % of said first non-zeolitic oxidic material consists of iron calculated as Fe2O3, with said second aqueous mixture prepared according to (ii), preferably adding water, to obtain a third aqueous mixture; (iv) disposing the third aqueous mixture obtained according to (iii) on a substrate, the substrate comprising an inlet end, an outlet end, an axial length of the substrate extending from the inlet end to the outlet end, and a plurality of channels defined by an inner wall of the substrate and extending therethrough; and optionally drying said substrate comprising said mixture; (v) calcining the substrate obtained in (iv).
11. The method of claim 10, wherein (i) comprises (i.1) preparing a mixture comprising water and the copper source, wherein the mixture preferably further comprises an acid, more preferably an organic acid, more preferably acetic acid; (i.2) adding said precursor of said second non-zeolitic oxidation component to said mixture obtained according to (i.1) to obtain said first aqueous mixture.
12. The method according to claim 11, wherein 90 to 100 wt. %, preferably 93 to 99 wt. %, more preferably 96 to 99 wt. % of the copper source is present in the mixture prepared in (i.1) in a non-dissolved state; The copper particles in the mixture according to (i.1) preferably have a Dv90 in the range of 0.1 μm to 15 μm, more preferably in the range of 0.5 μm to 10 μm, more preferably in the range of 1 μm to 8 μm, more preferably in the range of 3 μm to 7 μm.
13. A catalyst for selective catalytic reduction of NOx, the catalyst being obtainable by or obtained by the method according to any one of claims 10 to 12.
14. An exhaust gas treatment system for treating exhaust gases leaving a compression ignition engine, preferably a diesel engine, the exhaust gas treatment system having an upstream end for introducing the exhaust gas flow into the exhaust gas treatment system, wherein the exhaust gas treatment system comprises a catalyst according to any one of claims 1 to 9 and 13 and one or more of a diesel oxidation catalyst, a selective catalytic reduction catalyst, an ammonia oxidation catalyst, a NOx trap and a particulate filter.
15. A system according to claim 14, comprising a diesel oxidation catalyst, wherein a catalyst according to any one of claims 1 to 9 and 13 is located downstream of the diesel oxidation catalyst.
